Akibat Hukum Perusahaan Gagal Bayar Terhadap Nasabah Pemegang Polis - Kembaren, Keny Indah Gloria (Faculty of Law, University of Mataram, 2023)
From January 2008 to September 2020, at least five life insurance companies failed to pay K Life Insurance (after this, referred to as